COMPARISON OF C2WP BOUREAL LAKES PROCESSOR AND REGIONAL WATER PROCESSOR ALGORITHM ON EXTRACTING ESTIMATED TOTAL SUSPENDED SOLID DATA OF LAKE SENTANI - Jaelani, Lalu Muhamad; Syariz, M. Aldila (Geoid, 2015)
Lake Sentani is one of fifteen Indonesian National Priority Lakes. In the Jurnal Biologi Papua, Surbakti (2011) said that Lake Sentani is an euthropic lake. MEdium Resolution Imaging Spectrometer (MERIS) is one of a few sensors at Envisat Satellite which is used to monitor water-quality conditions. At BEAM VISAT, MERIS image can be processed using 3 algorithms to extract water-quality. Those algorithms are Case-2 Water Processor (C2WP) Euthropic Lakes, Case-2 Water Processor (C2WP) Boureal Lakes, and Regional Water Processor Water Processor (WP). In this research, we compared the performance of C2WP Boureal and Regional WP on extracting Total Suspended Solid (TSS) data. Extracting TSS data using C2WP Euthropic were used as data validation because Lake Sentani was an euthropic lake.